Bergamot Essential Oil Effect against Candida Albicans Activity on Heat Cure Acrylic Denture Base - Zinah Salah Mawlood1, Ghassan Abdul-Hamid Naji2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the current study is to evaluate the antifungal efficacy of several different percentages of Bergamot Essential Oil (BEO) incorporated into heat cure PMMA denture base material against Candida albicans. Materials and Method: Eighty samples were divided into eight groups including six various percentages of BEO (2%,3%, 4% ,5%, 6% and 7% by volume) and 0% BEO as a control group, in addition to 1.4% by weight of nystatin which represent the positive control group. All these additives were incorporated into heat cure PMMA denture material. After 48h incubation in distilled water, all samples were assessed by Candida albicans colonies viable count test. Results: For Candida albicans activity test; the experimental groups (2%,3%, 4%, 5%, 6% and 7% of BEO) showed highly significant decrease in the mean values of the viable count of Candida albicans when compared to the control group (0% BEO) (p<0.01). In contrast, a non-significant difference among experimental groups and 1.4% nystatin group. Conclusion: Bergamot essential oil was successfully incorporated into heat cure PMMA denture base material and could act as potential antifungal agent with a drug delivery system against Candida albicans. It seemed that adding of 5% and 6% BEO was the most beneficial effects against the growth of fungi.